Synthesis of Water-Soluble Menthol Derivatives Using Response Surface Methodology - Nisar, Shafaq; Hanif, Muhammad Asif; Rashid, Umer; Jilani, Muhammad Idrees; Bhatti, Ijaz Ahmad; Ali, Imtiaz; Zieniuk, Bartłomiej (Indonesian Journal of Chemistry, 2024)
In this study, menthol was glycosylated with starch in the presence of α-amylase to produce menthyl maltoside (MenM) as the primary product. Optimization of the experimental parameters, including the menthol-starch ratio, enzyme concentration, temperature, and time, was performed using response surface methodology (RSM). The RSM-generated model displayed adequate accuracy and reasonable predictability for the MenM yield under the specified experimental conditions. Under the optimized reaction conditions of the menthol-to-starch ratio of 1:3 (50 °C, 18 h) and enzyme concentration of 50 U, the highest yield of MenM (23.7%) was obtained. Fourier transform infrared and nuclear magnetic resonance spectroscopies were employed to analyze the synthesized menthol derivative MenM. Compared with standard menthol, the synthesized menthol derivatives displayed various biological activities, including antioxidant, antibacterial, antifungal, and insecticidal properties. The results of this study demonstrate the effectiveness of RSM-optimized synthesis of MenM from the glycosylation of menthol with starch. This study showed that MenM is highly soluble in water and can be easily stored owing to its non-volatile nature.